miR-1-3p suppresses the epithelial-mesenchymal transition property in renal cell cancer by downregulating Fibronectin 1 - Liu, Jianghui (Cancer Manag Res, 2019)
PURPOSE: Renal cell cancer (RCC) is one of the primary causes of malignancy deaths all over the world. The most important cause of RCC-related mortality is metastasis. Epithelial-mesenchymal transition (EMT) plays an important role in metastasis of malignant tumors including RCC. miR-1-3p is confirmed to be decreased in many types of cancer. Nevertheless, the function of miR-1-3p in RCC metastasis and EMT process was still unclear. MATERIALS AND METHODS: In this study, information from clinical investigation, in vitro study, and in vivo study discovered miR-1-3p expression character and its status in RCC. The character of miR-1-3p in invasive and metastatic properties in vitro and in vivo was also inspected in RCC cells and xenograft tumor model, and expression levels of EMT markers were evaluated in RCC cells and tissues. RESULTS: miR-1-3p was proved to be decreased in RCC cell lines and tissues compared with normal renal cells and tissues. miR-1-3p expression level in RCC tissues was closely related with capsulation, lymph node metastasis, and vascular invasion. miR-1-3p was found to be able to block the EMT process in A498 and CAKI-1 RCC cells and tumors. Luciferase reporter assay and expression level rescue assays were employed to reveal that miR-1-3p inhibited the invasion and migration property of RCC cells by directly targeting Fibronectin 1. Upregulation of Fibronectin 1 partially reversed the suppressive effect of miR-1-3p on EMT process. CONCLUSION: In brief, this study has verified that miR-1-3p blocked the EMT process of RCC cells by reducing Fibronectin 1 expression. miR-1-3p/Fibronectin 1 axis may be considered as a new target for drug development of RCC.